Handbook of research on digital transformation, industry use cases, and the impact of disruptive technologies - Wynn, Martin George, 1951- (Advances in e-business research series., 2022)
"This book examines the phenomenon of digital transformation and the impact of disruptive technologies through the lens of industry case studies, where different combinations of these new technologies have been deployed and incorporated into enterprise IT and business strategies"--